2023
DOI: 10.1101/2023.07.20.549958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Membrane mechanics dictate axonal morphology and function

Abstract: Axons are thought to be ultrathin membrane cables of a relatively uniform diameter, designed to conduct electrical signals, or action potentials. Here, we demonstrate that unmyelinated axons are not simple cylindrical tubes. Rather, axons have nanoscopic boutons repeatedly along their length interspersed with a thin cable with a diameter of ~60 nm like pearls-on-a-string. These boutons are only ~200 nm in diameter and do not have synaptic contacts or a cluster of synaptic vesicles, hence non-synaptic. Our in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
2
1
0
Order By: Relevance
“…Of note, secretory vesicles are separated by extremely narrow (∼50–60 nm) cytoplasmatic bridges, sufficient for few microtubules to pass through. A similar type of organization was also recently observed in some rodent axons ( Griswold et al, 2023 ). How these vesicles are transported to these locations or maintained is unclear.…”
Section: Chemical Synapses and Signaling In Ctenophores Vs Direct Ret...supporting
confidence: 82%
“…Of note, secretory vesicles are separated by extremely narrow (∼50–60 nm) cytoplasmatic bridges, sufficient for few microtubules to pass through. A similar type of organization was also recently observed in some rodent axons ( Griswold et al, 2023 ). How these vesicles are transported to these locations or maintained is unclear.…”
Section: Chemical Synapses and Signaling In Ctenophores Vs Direct Ret...supporting
confidence: 82%
“…Of note, secretory vesicles are separated by extremely narrow (~50-60 nm) cytoplasmatic bridges, sufficient for few microtubules to pass through. A similar type of organization was also recently observed in some rodent axons 41 . How these vesicles are transported to these locations or maintained is unclear.…”
Section: Chemical Synapses and Signaling In Ctenophores Vs Direct Ret...supporting
confidence: 81%
“…As we have demonstrated, the geometry of the axon, especially the diameters at branching points, has a significant influence on spike filtering. Previous studies showed activity-dependent plasticity of axonal diameters and bouton sizes that affect action potential conduction velocity ( Chéreau et al, 2017 ; Griswold et al, 2023 ). Here we suggest that these dynamical changes in axonal dimensions may affect not only the velocity of action potential propagation but also filtering properties.…”
Section: Discussionmentioning
confidence: 99%